Efficiency of biological insecticides against the main pests of winter wheat in the system of organic farming - Zaiets, S.; Kovalenko, A.; Onufran, L.; Yuzyuk, S.; Fundirat, K. (Quarantine and plant protection, 2023)
Goal. To investigate the pest infestation of soft winter wheat (Triticum aestivum L.) crops and to determine the technological effectiveness of biological products against them in the system of organic farming. Methods. Field studies to record the number of major pests of winter wheat before and after 10 days after treatment with biological insecticides were laid out and conducted in a six-man rotation of organic farming: peas — soft winter wheat — chickpeas — hard winter wheat — oil flax — millet. The winter wheat crops were treated twice in BBCH 31 and BBCH 59. The technical effectiveness of biological insecticides was determined and compared with chemical insecticides, and the reliability of the results obtained was determined using the mathematical and statistical method in the Agrostat program. Results. The studies of 2021—2023 on the control variant (without treatment) of winter wheat observed an average of 1.1 copies/ m2 of the shell bug (Eurygaster integriceps Put.), 17.4 copies/stem of cereal aphids (Schizaphis graminum F.), 7.7 copies/ear of wheat thrips (Haplothrips tritici Kurd) and 4.5 copies/ m2 of bread beetle (Anisoplia austriaca Hrbst.), and on variants treated with biological insecticides — by 27.3—36.4%, respectively, 36.8—39.5, 40.6—50.7 and 33.3—46.7% less. The technical efficiency of biological preparations against the indicated pests in the years of research ranged from 10.0 to 68.8%, and that of chemical insecticides from 55.6 to 100.0% and depended on both the conditions of the year and the type of pest and the preparation. Among biological insecticides, the highest technical efficiency against the turtle bug and wheat thrips on winter wheat crops was provided by Bitoxybacillin-BTU, r. (10 l/ ha) — 31.6 and 53.2%, respectively, and against cereal aphids (37.5%) and bread beetle (47.5%) — Biospectr BT, r. (3 l/ha) with Metarizin BT, r. (3 l/ ha). Bioinsecticide Phytoimun Sintez, r. (1 + 1 l/ha) against the specified pests had somewhat lower technical efficiency — 23.3 and 45.3% and 33.8 and 33.0%, respectively. Conclusions. The use of biological insecticides Bitoxybacillin-BTU, p. (10 l/ha), Biospectr BT, p. (3 l/ ha) with Metarizin BT, p. (3 l/ ha) and Phytoimun Sintez, p. (1 + 1 l/ha) on soft winter wheat crops in organic farming rotation makes it possible to reduce the number of shell bugs and cereal aphids by 1.4—1.6 times, and wheat thrips and bread beetle by 1.7—2.0 and 1.5—1.9 times compared to the control.